CFD analysis of intake flow in the L-head engine - Mohd Shafie, Abdul Muhaimin (2017)
The CNG fuel engine usually had lower performance comparing to gasoline fuel. A small single cylinder engine (L-head engine) is used in Green Technology Vehicle laboratory (GTeV) lab, which is low cost and commonly available in the market. It is difficult to experimentally to track the particle in 3D cases. Therefore, commercial numerical simulation is used. This thesis analysed the behaviour of the flow inside L-head combustion chamber for in-cylinder engine without the combustion with three different models were simulated. The objectives are to develop numerical model, to investigate the flow without combustion, to analyse flow with CNG and gasoline and to perform validation on the pressure between experiment and simulation. There are three types of simulation; steady, Port-flow and Cold-flow. The engine parameters and valve lift are measured, and the engine head were scan using ezScan 4.5 software. All of the simulations are simulated using ANSYS software. Only intake stroke is simulated for steady simulation with different crank angle and engine speed. Port-flow simulation is only simulated at intake stroke with introduction of CNG and gasoline as a fuel and three different valve lift. Cold-flow simulated a full cycle engine without combustion process. The Steady simulation is dealing with the static domain. There are only combustion chambers and piston volume involved in the steady simulation. The air inlet velocity was calculated using the standard engine formula for different piston position. The second simulation, Port-flow simulation also deals with the static geometry domain. Inplenum and outplenum was added by the presence of both intake and exhaust valve for the Port flow simulation domain. Three different valve lift was chosen. Gasoline and CNG were used as fuel, which enters the domain through the fuel intake. The last simulation is called Cold-flow where the geometry is moving according to the crank angle. The intake valve and exhaust valve are moving according to the measured valve profile. Meanwhile the piston movement was generated according to the crank angle of the engine. The result of steady flow simulation shows the velocity is high when the piston position is at 45° and engine speed of 4500 rpm. The result of Port-flow simulation shows the mass flow rate and velocity across the domain increase as the valve lift increase. The pressure difference between the intake port and combustion chamber decrease as valve lift increase. The swirl ratio decreases as going down the cylinder. The Cold-flow result shows the turbulence kinetic energy, swirl, tumble, and cross-tumble ratio inside the combustion chamber increase in the middle of the intake stroke. The temperature inside combustion chamber is increasing as the piston reaches TDC due to compression process. The result of Cold-flow simulation is validated by experiment without combustion with 22.73% of percentage difference at peak pressure. The combustion chamber head has been scanned and imported to ANSYS software. The velocity is highest when the piston located at the middle of the stroke and lowest then the piston approaching TDC and BDC. The flow pattern of gasoline and CNG has no significant change. The pressure for experiment and Cold-flow simulation is validated through its pressure pattern.